The network of international student mobility: Enlargement and consolidation of the European transnational education space? - Eva Maria Vögtle; Michael Windzio (Universität Bremen, Collaborative Research Center 597 - Transformations of the State, 2015)
In this paper, we investigate the impact of membership in the Bologna Process on patterns and driving forces of cross-national student mobility. Student exchange flows are analyzed for Bologna Process member states and non-Bologna OECD members over a ten-year period (from 2000 to 2010). We apply a social network approach focusing on outbound diploma-mobility. Based on social network analyses, we first visualize the exchange patterns between sampled countries. In doing so, we analyze the student exchange linkages to first gain descriptive insights into the development of the network. Second, we use exponential random graph models (ERGM) to test which factors determine transnational student mobility. The results of our network analyses reveal that cross-national student exchange networks are stable over time. At the core of these networks are the United States, Great Britain, France, and Germany; they attract the highest shares of students from the remaining countries in our sample. Moreover, the results of the ERGM demonstrate that homophily between countries determines student exchange patterns. The most relevant ties exist between bordering countries. Moreover, membership in the Bologna Process impacts mobility patterns, but surprisingly, it has a mitigating effect. – – In diesem Beitrag untersuchen wir den Einfluss der Mitgliedschaft im Bolognaprozess auf Muster internationaler Mobilität von Studierenden. Über eine Periode von 10 Jahren (2000 bis 2010) wird der internationale Austausch von Studierenden sowohl für Länder analysiert, die sich dem Bolognaprozess verpflichtet haben, als auch für Länder, bei denen dies zum jeweiligen Zeitpunkt (noch) nicht der Fall war. Wir bilden die internationale Verflechtung von 41 Ländern als Netzwerke ab, die aufgrund von Strömen von Studierenden entstehen. Im ersten Schritt stellen wir die Verflechtungen grafisch dar und beschreiben die Veränderung des Netzwerkes über die Zeit. Sodann schätzen wir Exponentielle Zufallsgraphenmodelle (p*) und testen, welche Faktoren die Verflechtung bestimmen. In den empirischen Analysen zeigt sich, dass das untersuchte Netzwerk vergleichsweise stabil ist. Im Zentrum des Netzwerkes stehen die Länder USA, Frankreich, Großbritannien und Deutschland. Dies sind die häufigsten Ziele der studentischen Mobilität. Die Ergebnisse weisen zudem darauf hin, dass sich die Mobilität eher zwischen Ländern mit ähnlichem ökonomischen Leistungsniveau abspielt. Den stärksten Effekt weist die gemeinsame Grenze auf, d.h. die räumliche Nähe in Form von direkter Nachbarschaft ist letztlich entscheidend. Auch die Mitgliedschaft im Bologna-Raum hat einen Einfluss, der aber interessanterweise über die Zeit abzunehmen scheint.
Keywords: 300